An Assessment of a Proposed Multi-Pillar Pension Reform in Peru - Olivera, Javier (2016)
This article estimates and analyses the potential fiscal and distributiveeffects of a proposal to transform the current Peruvian pension system intoa multi-pillar pension system. In this new system, part of the contributionswould go to a solidarity fund to finance minimum pensions, and the rest toindividual retirement accounts. The simulation of actuarial liabilities andfuture distributions of pensions are performed using random samples fromthe database of administrative records of individuals insured by the Peruvianpublic and private pension systems as at December 2013. This study analysesthe effects of the reform on actuarial liabilities, inequality of pensions, andoverall wellbeing of pensioners, in order to illustrate the different trade-offsinvolved in pension reform. At the same time, the explicit inclusion of normativejudgments in the evaluation of welfare functions makes it possible to determinethat a multi-pillar pension system is better than the current one, even underthe stringent condition of no aversion to inequality.